(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the characteristics of patients using fibrinolytics medicine - Alteplase in the treatment of acute ischemic stroke. Subjects and methods: A retrospective cross-sectional and non-interventional study on 52 stroke patients using Alteplase at Can Tho City General Hospital from April 2019 to October 2020. Results: Male accounted for 53.8%, average age 58.31 years old. Risk factors included a history of hypertension (53.8%), diabetes (21.8%), stroke (6.4%), atrial fibrillation (2.6%), and smoking. (15.4%). Common clinical symptoms included weakness/hemiplegia (88.5%), speech disorder (84.6%), facial paralysis (82.7%), and sensory disturbances (71.2%) and oculomotor limitation (23.1%). Complications of extracranial hemorrhage (17%), progressive ischemic stroke (9.7%), allergies (4.8%), new embolism (2.4%) and no cerebral hemorrhage patient. The average NIHSS score at admission was 11.8 ± 7.1 points, decreasing at the time of 24 hours and discharge, respectively, 5.8 ± 5.3 and 4.2 ± 5, 5 points. The difference was statistically significant between the study times. Conclusion: The average age of patients was 58.31 years old, mainly men. Hypertension, diabetes, and smoking were the most common risk factors. Weakness/hemiplegia, speech disorder, facial paralysis, and sensory disturbances were common symptoms. The NIHSS score decreased gradually at 24 hours after admission and at discharge compared with the time of admission.